2009
DOI: 10.3162/036298009789869709
|View full text |Cite
|
Sign up to set email alerts
|

Making a Good Impression: Resource Allocation, Home Styles, and Washington Work

Abstract: Members of Congress engage in a variety of representational activities, but existing research suggests that the effect of these activities on reelection margins is mixed. Reframing the question, we examined whether or not constituents notice the home styles of members and members' efforts to communicate their activities through the allocation of official resources. Combining new data on members' office expenditures with data from the American National Election Studies, we found evidence that constituents perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Explanation of Washington activities is one of the three components of a legislator's “home style” identified by Fenno (). The other two components, presentation of self and allocation decisions, have received significantly more scholarly attention (e.g., Adler ; Adler, Gent, and Overmeyer ; Evans , ; Fiorina and Rohde ; Grimmer ; Grimmer, Messing, and Westwood ; Grose ; Lipinski ; Parker and Goodman ; Sinclair ). The lack of systematic study of explanations is surprising.…”
Section: Theory: Explanations and Representationmentioning
confidence: 99%
“…Explanation of Washington activities is one of the three components of a legislator's “home style” identified by Fenno (). The other two components, presentation of self and allocation decisions, have received significantly more scholarly attention (e.g., Adler ; Adler, Gent, and Overmeyer ; Evans , ; Fiorina and Rohde ; Grimmer ; Grimmer, Messing, and Westwood ; Grose ; Lipinski ; Parker and Goodman ; Sinclair ). The lack of systematic study of explanations is surprising.…”
Section: Theory: Explanations and Representationmentioning
confidence: 99%
“…Similarly, Rocca and Gordon (2010) characterize bill sponsorship as position taking that is undertaken in order to signal support for issues of concern to "members of an attentive public" (i.e., interest groups); such groups, in turn, reward legislators with campaign contributions. Surveys of constituents also find that individuals' ability to identify a reason for liking their House member is positively related to the number of bills introduced by the member of Congress (Box-Steffensmeier et al 2003;Parker and Goodman 2009). Taken as a whole, this research suggests that members of Congress will sponsor or co-sponsor court-curbing bills when it suits their electoral needs.…”
Section: Court Curbing As Position Takingmentioning
confidence: 67%
“…Cover and Brumberg (1982) conducted a field experiment with randomized distribution of government pamphlets and found that receiving a pamphlet increased name recognition and evaluations of incumbent members of Congress. Parker and Goodman (2009) show that House members who engage in high levels of franking are rated more favorably on constituency service by survey respondents in the American National Election Study (ANES). I conceptualize franking as primarily an attempt to improve the valence of House incumbents.…”
Section: Background On Constituency Communicationmentioning
confidence: 99%
“…I study how the electoral environment affects the intensity of this constituency communication by examining how House members' expenditures on mass mailings and communication respond to changes in their electoral security. The volume of constituency communication is important because it has the potential to affect citizens' evaluations of House members (Cover and Brumberg 1982;Parker and Goodman 2009). As one prominent example, Grimmer, Messing, and Westwood (2012) use a field experiment to show that repeated credit-claiming messages improve citizens' feelingthermometer ratings of congressional incumbents.…”
mentioning
confidence: 99%